Quality assessment of shrub observation data based on TLS: A case of revegetated shrubland, Southern Qinghai‐Tibetan Plateau. (20th December 2022) - Tian, Jiarong; Li, Haidong; Sun, Xinyu; Zhou, Youfeng; Ma, Weibo; Chen, Junsong; Zhang, Jing; Xu, Yannan
Abstract: Vegetation restoration is one of the effective measures to deal with land degradation, and shrubs, as the pioneer plants, can improve soil conditions and accelerate the recovery of desertification. In recent decades, single‐scan (SS) and multiple‐scan (MS) modes have been widely used for forest inventories by terrestrial laser scanner (TLS) but TLS‐based shrub observation, and data quality uncertainties are less studied, especially in eco‐fragile regions with high survey costs and harsh environmental conditions. In this study, two shrub sample plots with different topographic characteristics were selected as the study area in the southern Qinghai‐Tibetan Plateau. We compared the basic phenotypic parameters (BPPs) under SS and MS mode, including number (N), height (H) and crown width (CW), to evaluate the potential of SS mode in extracting vegetation attributes. Through the distribution of shrub information loss rate (L) with distance and shrub height, the limitations of SS mode in obtaining data were discussed. By combining the topographic features of scanning spots, topographic relief (T) and L, we provided reasonable opinions on TLS collection mode, setting of scanning spots, and other operational aspects. The results indicated that: (1) SS mode has good applicability in shrub observation under different terrain characteristics. (2) The height distribution of the shrub is the main factor affecting the quality of data collection, and the information loss bias caused by distance should be considered only in the shrub plots with uniform height distribution. (3) T has an impact on shrub growth but has no effect on the quality of data acquisition (no significant correlation between T and L). These findings will provide technical support for TLS data collection on ecological restoration of degraded grassland dunes.